Study Of Community Legal Culture From The Perspective Of River Maintenance In Banjarmasin City - Listiyani, Nurul; Nopliardy, Rakhmat (International Journal of Educational Research & Social Sciences, 2024)
Background:The problem of river water resource management between upstream and downstream areas is a problem in the era of decentralization and regional autonomy. The era of regional autonomy has changed various authorities in the environmental sector which are increasingly limited at the central and provincial government levels but have become greater at the Regency/City level. Law Number 23 of 2014 concerning Regional Government basically places the authority of the Regency/City Regional Government.Methods:The primary data obtained from the researcher's field research is expected to be able to answer these objectives. Furthermore, with secondary data, the researcher will conduct an inventory of primary legal materials in the form of regulations at both the national and regional levels that regulate river management and how the legal culture of the Banjarmasin City community utilizes and maintains rivers.Findings:The river culture in Banjarmasin City is not only marked by community activities carried out on the river, but also marked by the presence of settlements on the banks of the river, such as residential areas, places of worship, floating markets, siring, museums and other places on the banks of the river. In each sub-district there is a river caretaker whose job is to maintain and preserve it and as the first party to report if there is a problem related to the river. Conclusion:River culture is certainly a demand for society to be able to maintain the sustainability of rivers, because culture is not only about the activities and characteristics of a society, but is also seen from the behavior of its people in utilizing rivers, because rivers as a source of life must of course be utilized properly.Novelty/Originality of this article:An environmentally aware culture is crucial to improve so that there are no more people who do not care about preserving rivers and throwing garbage into rivers. River culture is certainly a demand for society to be able to maintain the sustainability of rivers, because culture is not only about the activities and characteristics of a society, but is also seen from the behavior of its people in utilizing rivers, because rivers as a source of life must of course be utilized properly.